1992
DOI: 10.1097/00001888-199201000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Womenʼs attitudes toward careers in academic medicine at the University of California, San Francisco

Abstract: In order to identify the concerns and possible barriers for women considering careers in academic medicine, in 1990 the authors surveyed both men and women medical students, housestaff, postdoctoral students, and junior faculty at The University of California, San Francisco (UCSF). The authors achieved a 58% response rate from students and faculty, a 21% response rate from postdoctoral students, and a 15% response rate from housestaff. Results indicated that women at all levels were less interested in academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 0 publications
1
53
1
2
Order By: Relevance
“…(20,28) In our study, the main reasons why interns did not have mentors were a lack of time or difficulty in developing a mentoring relationships with their superiors, rather than a lack of potential mentors. Therefore, organising formal mentoring programmes would be in the interest of interns, as this would encourage the participation of both mentors and mentees, with an aim to provide ongoing guidance, and to monitor and evaluate the effectiveness of mentoring.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…(20,28) In our study, the main reasons why interns did not have mentors were a lack of time or difficulty in developing a mentoring relationships with their superiors, rather than a lack of potential mentors. Therefore, organising formal mentoring programmes would be in the interest of interns, as this would encourage the participation of both mentors and mentees, with an aim to provide ongoing guidance, and to monitor and evaluate the effectiveness of mentoring.…”
Section: Discussionmentioning
confidence: 66%
“…In earlier studies, men were found to be more likely than women to have a positive experience with regard to their mentoring relationship. (17,20,21) However, Fried et al have reported that multifaceted mentoring interventions that eliminate gender-based obstacles markedly improve women's mentoring experiences, and lead to women's promotion and retention in academic medicine, compared to men. (21) Effective mentoring thus greatly influences the career success of women.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of "clock stopping" for tenure track physicians has been implemented at the majority of Universities 17,18 . While the intention of this policy was to be supportive of women faculty, delaying promotion following an already extended training time period can be construed as punitive, particularly for faculty who are diligently working both at work and at home.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Findings from a study of University of California (UC) faculty may provide some insight into this retention phenomenon, showing that a female faculty member was less likely to make tenure than a male if she had a child within 5 years of taking a tenure-track faculty position. 9 Available data from other sources also suggest that the academic productivity of early career female faculty in medicine is adversely and differentially affected by child-rearing responsibilities. Indeed, female faculty with children overwhelmingly believe that their career progress and productivity has been slowed by having children.…”
Section: Introductionmentioning
confidence: 99%